1977
DOI: 10.1111/j.1532-5415.1977.tb00663.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Mental Illness in the Aged: Unmasking the Effects of a Diagnosis of Chronic Brain Syndrome

Abstract: A combination of three psychiatric screening tests was used to uncover the extent of affective-psychotic symptoms, the indications of "chronic brain syndrome," and the perceptual limitations among two selected populations of elderly persons. It was found that 25 percent of 48 residents in a home for the aged, and 9 percent of 45 members in a social club, had four or more affective-psychotic com-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

1982
1982
1991
1991

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 4 publications
0
13
0
1
Order By: Relevance
“…In 1962, Goldfarb' found 87% of the residents in nursing homes to have &dquo;chronic organic brain syndromes.&dquo; Over the last 20 years, a number of investigators have confirmed this observation. [2][3][4][5] Although informative, these studies have a number of limitations. First, none of the studies used psychiatric diagnostic criteria such as the Diagnostic and Statistical Manual, ed 3, Revised (DSM III-R) .6 Consequently, it is difficult to generalize these results to current concepts in psychiatric diagnosis.…”
mentioning
confidence: 99%
“…In 1962, Goldfarb' found 87% of the residents in nursing homes to have &dquo;chronic organic brain syndromes.&dquo; Over the last 20 years, a number of investigators have confirmed this observation. [2][3][4][5] Although informative, these studies have a number of limitations. First, none of the studies used psychiatric diagnostic criteria such as the Diagnostic and Statistical Manual, ed 3, Revised (DSM III-R) .6 Consequently, it is difficult to generalize these results to current concepts in psychiatric diagnosis.…”
mentioning
confidence: 99%
“…O FHT-R mostrou-se um instrumento útil para detectação de distúrbios orgânicos em diferentes ambientes de estudo 6,7,13 e opera relativamente bem sem muita interferência de fatores culturais. Neste estudo piloto a versão reduzida do FHT mostrou-se mais específico do que sensí-vel (a sensibilidade foi 60% e a especificidade 94%).…”
Section: Discussionunclassified
“…The FHT-R has been regarded as a useful test for the clinical assessment of organic mental disorder in a variety of settings 6,7,13 , and it is a relatively "cultural free" examination. In this pilot study the reduced version of the Face-Hand Test was shown to be a more specific than sensitive test (the sensitivity was 60% and the specificity 94%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the psychopathology of dementing disorders have demonstrated that depressive manifestations occur in approximately half of the demented patients (Ernst et al, 1977). In a recent series reported by Wragg and Jeste (1989), about half of the Alzheimer's patients had depressed mood.…”
mentioning
confidence: 98%